Addiction psychiatry and COVID-19: impact on patients and service provision. (21st September 2020) - Columb, D.; Hussain, R.; O'Gara, C.
Abstract : The Coronavirus Disease 2019 (COVID-19) pandemic has undoubtedly had a major impact on the provision of physical healthcare in Ireland and worldwide. The mental health impact of this pandemic cannot be underestimated, particularly relating to patients suffering from addiction. Heightened public stress and anxiety levels, increasing isolation and the physical consequences of addiction play a large role in the proliferation and ongoing relapse of substance misuse and behavioural addiction. Service provision is an ongoing challenge not only due to the increasing need for services given the increased mental health burden of COVID-19 but also the restrictions in place in clinical areas to achieve social distancing. The necessary adaptations to service provision provide opportunities for the analysis of current processes used in our addiction unit and the introduction of new processes to our service. The current crisis tests the sustainability of the service to provide the high standard of care required for these patients.